The Influence of Product Quality and Price on Customer Loyalty Through Customer Satisfaction as a Mediator on Wardah BB Cream Products in Padang City - Fanesa Azara Putri; Fitria Ridhaningsih (Pusat Riset dan Inovasi Nasional, 2025)
The cosmetic industry in Indonesia continues to experience significant development along with the increasing awareness of the community, especially women, towards appearance. This change continues to grow also because the modern lifestyle today increasingly demands an attractive appearance as a form of self-confidence, both for daily and professional activities. This drives consumer interest in quality cosmetic products at affordable prices. In addition, awareness in choosing safe products to use according to skin needs is also increasing, this is in line with the education provided by cosmetic products through the marketing they use.